Novel ultra-wideband microstrip meandered-loop antenna - LV Wen-jun; CHENG Chong-hu; ZHU Hong-bo (Tongxin xuebao)
A novel meandered-loop ultra-wideband antenna was proposed.The antenna was similar in configuration with a conventional wide-slot antenna,however,by employing meandered-loop structure,not only ultra-wideband performance but also compact size could be achieved.It had been investigated both numerically and experimentally for its input performance and radiation characteristics.It is observed that an operation bandwidth of over 4:1 has been achieved.Furthermore,relative stable and good omnidirectional radiation performance have also been achieved.Thus it can be determined as a useful candidate for UWB application.